XIAL-FLUX PERMANENT MAGNET SYNCHRONOUS GENERATORS FOR WIND TURBINE APPLICATIONS - Virtič, Peter; Pišek, Peter; Štumberger, Bojan; Hadžiselimović, Miralem; Marčič, Tomaž (Journal of Energy Technology, 2024)
This paper presents an axial-flux permanent magnet generator (AFPMSG) with coreless stator for wind turbine applications. In the introductionof this paper, a surve yofexistent wind turbine generators with regards to their advantages and disadvantages is presented. An overview of generators is based on many wind generatorsystems built during previous decades, whichare stillinoperation. In recentyears, the technologies for exploitingthe wind energy have rapidly developed and avarietyof wind generator systems is available to day on the global market. The selection of appropriate wind generator system mainly depends on the user demands, operating conditions, level of production difficulty and costs. Further, the dependencies between geometrical design and characteristics of coreless stator AFPMS Garepresented. Due to the absenceofcoggingtorque, the corelessstator AFPMS Gisavery useful generator design, especiallyatlow wind speeds.